The effectiveness of project-based learning: a retrospective comparative analysis of Russian and foreign experience - Astratova, Galina Vladimirovna; Gorelova, Galina Victorovna; Makarenya, Tatyana Anatolyevna; Matveeva, Ludmila Grigoriena; Kalinichenko, Alexei Igorevich; Onwusiribe, Chigozirim Ndubuisi (Frontiers in Education, 2026)
BackgroundProject-based learning (PBL) implementation faces unresolved tensions between pedagogical integrity and economic utility, complicated by fragmented theoretical frameworks and divergent national approaches across educational systems.ObjectiveThis study identifies systematic barriers to PBL effectiveness through retrospective comparative analysis of Russian and international practices, models socio-economic impacts via cognitive simulation, and develops evidence-based optimization strategies.MethodsMixed-methods approach combining historical analysis of PBL evolution (fifteenth to twentieth centuries), institutional case studies from six leading Russian universities (HSE, SFedU, Moscow Polytech, FEFU, UrFU, UNN), and cognitive simulation modeling using 29-node framework with CMCS software to map regional development impacts across 24 test scenarios.Key findingsRussian PBL emphasizes collective outcomes while Western models prioritize individualization. Current implementations show 78% commercial focus over competency development, though customer-centric approaches demonstrate 3.2 × higher critical thinking scores. Cognitive modeling confirms PBL specialists enhance human capital (+210%), regional sustainability (+120%), and technological sovereignty (+150%) with grant support reducing risks by 37–52%.ConclusionPBL effectiveness requires rebalancing commercial-pedagogical tensions through customer-centric approaches, enhanced teacher training, and systematic grant support. Cognitive modeling provides unifying framework for resolving paradigm conflicts while maximizing socio-economic impact.